Curricularization of Extension at Instituto Federal de São Paulo: foundations, trajectory and current challenges - Sakano, Luciana Harumi dos Santos; Almeida, Marcelo Vilela de (Guará Journal, 2025)
This article examines the implementation of extension curriculum integration at the Federal Institute of São Paulo, in accordance with Resolution CNE/CES No. 7/2018. The study adopts a qualitative approach, grounded in action research and a case study methodology, and is based on a literature review, document analysis, and participatory observation in policy planning and management settings. The findings reveal significant progress in the institution’s extension efforts, including a substantial increase in extension projects, the establishment of institutional programs, and the integration of extension activities into all undergraduate courses, supported by institutional regulations. Moreover, there is a growing engagement with extension principles among faculty, students, and administrators. Nonetheless, persistent challenges remain, such as conceptual ambiguities about what characterizes an extension activity, the predominance of internal institutional logics over engagement with surrounding communities, and operational and structural limitations that hinder effective implementation. The study concludes that consolidating extension curriculum integration at IFSP requires more than regulatory frameworks; it calls for profound cultural, pedagogical, and institutional transformations to strengthen an extension-oriented academic culture and reaffirm higher education’s commitment to social transformation.
Keywords: Curricularization of Extension; Professional and Technological Education; Federal Institutes; Educational Policies; Extension Management